COVID-19 Coagulopathy with Superior Mesenteric Vein Thrombosis Complicated by an Ischaemic Bowel - Fan, Bingwen Eugene; Chang, Cheng Chieh Ray; Teo, Clarence Hai Yi; Yap, Eng Soo (Hämostaseologie, 2020)
COVID-19 coagulopathy is a hypercoagulable state which predisposes to venous, arterial and small vessel thrombosis. We describe a patient with COVID-19 who developed an acute superior mesenteric vein thrombosis with acute intestinal obstruction despite adequate anticoagulation.
Keywords: abdominal pain; COVID-19; hypercoagulability; anticoagulation; thrombosis